2019
DOI: 10.1038/s41589-019-0330-6
|View full text |Cite
|
Sign up to set email alerts
|

A PCBP1–BolA2 chaperone complex delivers iron for cytosolic [2Fe–2S] cluster assembly

Abstract: Hundreds of cellular proteins require iron (Fe) cofactors for activity, and cells express systems for their assembly and distribution. Molecular details of the cytosolic iron pool used for iron cofactors are lacking, but iron chaperones of the poly rC-binding protein (PCBP) family play a key role in ferrous ion distribution. Here we show that, in cells and in vitro , PCBP1 coordinates iron via conserved cysteine and glutamate residues and a molecule of non-covalently bound glutathione (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
73
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 52 publications
0
73
0
1
Order By: Relevance
“…It has been suggested that the labile iron pool is directed to some intracellular sites via protein chaperones [ 53 , 54 ], but a related possibility is direction via low molecular weight ternary glutathione complexes. Both mechanisms will be considered below.…”
Section: Intracellular Distribution Of Ironmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the labile iron pool is directed to some intracellular sites via protein chaperones [ 53 , 54 ], but a related possibility is direction via low molecular weight ternary glutathione complexes. Both mechanisms will be considered below.…”
Section: Intracellular Distribution Of Ironmentioning
confidence: 99%
“…Poly r C-binding protein 1 (PCBP1) binds iron and has been reported to deliver iron to specific proteins, for instance ferritin [ 53 ] and the cytosolic [2Fe-2S] cluster assembly [ 54 ]. In the latter interaction, iron is presented to PCBP1 as iron(II)glutathione, forming a ternary complex.…”
Section: Intracellular Distribution Of Ironmentioning
confidence: 99%
“…The moonlighting RNA-binding proteins PCBP1 and PCBP2 have been proposed to play a role in chaperoning cytoplasmic iron. 31,32 Labile iron can then be: (i) placed into cytosolic iron-containing proteins; (ii) transported to the mitochondria and incorporated into haem and Fe-S clusters; 2,33 (iii) sequestered inside ferritin (Ft); or (iv) exported to the extracellular space by FPN. 30 Nanocages of Ft, formed from 24 light (FtL) and heavy (FtH) subunits, provide a long-term storage site for iron, shielding the cell from potential redox activity of free iron.…”
Section: Iron In Biological Systemsmentioning
confidence: 99%
“…Free iron in the cytosol might partake in dangerous biochemical reactions; however, the factors that control trafficking of the cellular labile iron pool are only beginning to be understood. The moonlighting RNA‐binding proteins PCBP1 and PCBP2 have been proposed to play a role in chaperoning cytoplasmic iron 31,32 . Labile iron can then be: (i) placed into cytosolic iron‐containing proteins; (ii) transported to the mitochondria and incorporated into haem and Fe–S clusters; 2,33 (iii) sequestered inside ferritin (Ft); or (iv) exported to the extracellular space by FPN 30 .…”
Section: Iron In Biological Systemsmentioning
confidence: 99%
“…A recent study demonstrated that Pcbp1-deficient mouse embryos die at the peri-implantation stage [7], indicating an essential role of PCBP1 in mouse embryonic development. PCBPs are also important for iron metabolism, acting as iron chaperones [8][9][10][11][12][13][14]. Moreover, PCBP1 mediates proinflammatory cytokine production via stabilization of mRNA in iron-promoted CD4 + T-cell pathogenicity [15].…”
mentioning
confidence: 99%